Socio -Economic and Demographic Characteristics of Kadar Tribe of Anamalai Tiger Reserve - P J Suviera; M. Priya (Journal of Extension Education, 2024)
This article provides a descriptive glimpse into the socio-economic and characteristics of the Kadar tribe who live in all six settlements within the Pollachi division of Anamalai Tiger Reserve in Tamil Nadu viz., Kavarkkal, Nedungundru, Ethakuli, Erumparai, Theppakadu, and Udumanparai. The study reveals that the tribals have varying age distributions, gender and marital status. Primary education is the most common, with a significant portion engaged in agriculture. Low-income households rely on traditional livelihoods, and occupational diversity is limited. Access to government funds is limited, and housing consists of traditional 'kutcha' mud-houses.